Implementasi Media Pembelajaran Pop Up Dalam Menumbuhkan Literasi Membaca Siswa Kelas II - Huwaida Nahdah; Ngurah Ayu Nyoman Murniati; Mira Azizah; Ri’ah Nurhayati (Jurnal Riset Pendidikan Dasar (JRPD), 2024)
This research discusses the implementation of pop up learning media in increasing the reading literacy of class II students. This research aims to obtain an overview of the application of pop up learning media in improving students reading literacy, where this research method with a descriptive qualitative approach, where the researcher makes factual, accurate, and systematic descriptions of the event being researched. This research data collection used observation, interviews, and documentation. The data sources for this research are class II students and class teachers. The result of this research conclusion show that the implementation of pop up learning media in increasing the reading literacy of class II students can be said to be successful in using pop up learning media in a real way which can increase students reading literacy where the application of pop up learning media c